(untitled) (Malaysian Journal of Learning and Instruction, 2021)
Purpose â€“ This mixed-method study investigated the ways smartphone apps promote studentsâ€™ interaction, collaboration and learning performance. Methodology â€“ A total of 160 respondents from a Lithuanian university were identified using convenience sampling. A survey was conducted to explore the frequent activities involving interaction, collaboration and learning performance. Focus group interviews were also conducted to determine the apps used in their interactions. Findings â€“ The quantitative results suggest that the smartphone apps promote students’ interaction, collaboration and improved learning performance. Qualitative results indicate three types of apps that are commonly used for interactions by the undergraduates in Lithuania, namely educational, communication and entertainment apps. Significance â€“ The findings suggest that the instructions can play a constructive role in mediating the learnersâ€™ interactions on smartphone apps. As such, the study creates space for instructors to further craft pedagogical practices to better account for learnersâ€™ access to smartphone apps. It is hoped that this study will provide a path for educational solutions for instructors and practitioners.